Discovery and initial optimization of alkoxyanthranilic acid derivatives as inhibitors of HCV NS5B polymerase. Issue 2 (15th January 2017) - Parcella, Kyle; Nickel, Andrew; Beno, Brett R.; Sheriff, Steven; Wan, Changhong; Wang, Ying-Kai; Roberts, Susan B.; Meanwell, Nicholas A.; Kadow, John F.
Graphical abstract: Abstract: Alkoxyanthranilic acid derivatives have been identified to inhibit HCV NS5B polymerase, binding in an allosteric site located at the convergence of the palm and thumb regions. Information from co-crystal structures guided the structural design strategy. Ultimately, two independent structural modifications led to a similar shift in binding mode that when combined led to a synergistic improvement in potency and the identification of inhibitors with sub-micromolar HCV NS5B binding potency.